2005
DOI: 10.1108/13598540510606232
|View full text |Cite
|
Sign up to set email alerts
|

The impact of supply‐chain management capabilities on business performance

Abstract: PurposeThe purpose of this article is to empirically test the impact of supply‐chain management (SCM) capabilities on business performance so as to determine to what degree customer‐oriented SCM issues influence competitive position and organizational performance.Design/methodology/approachA rigorous methodology is employed to generate a reliable and valid measurement instrument. Responses from 474 manufacturing managers are then utilized to test a causal model using LISREL®.FindingsThe results indicate signif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
157
10
3

Year Published

2006
2006
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 211 publications
(187 citation statements)
references
References 45 publications
11
157
10
3
Order By: Relevance
“…Curkovic et al, 2000;Fawcett et al, 2000;Rosenzweig et al, 2003;Swink et al, 2005;Tracey, 2005;Jacobs et al, 2007;Lau Antonio et al, 2007;Swink et al, 2007). In fact, it has even been indicated that it is now conventional wisdom that superior manufacturing capabilities in dimensions of quality, delivery, flexibility, and cost enhance organizational performance as measured by market and financial performance (Rosenzweig et al, 2003).…”
Section: Manufacturing Capabilities and Organizational Performancementioning
confidence: 99%
See 1 more Smart Citation
“…Curkovic et al, 2000;Fawcett et al, 2000;Rosenzweig et al, 2003;Swink et al, 2005;Tracey, 2005;Jacobs et al, 2007;Lau Antonio et al, 2007;Swink et al, 2007). In fact, it has even been indicated that it is now conventional wisdom that superior manufacturing capabilities in dimensions of quality, delivery, flexibility, and cost enhance organizational performance as measured by market and financial performance (Rosenzweig et al, 2003).…”
Section: Manufacturing Capabilities and Organizational Performancementioning
confidence: 99%
“…Li, 2000;Fawcett et al, 2000;Tracey, 2005;Yu et al, 2014); however, results are mixed (e.g. Lau Antonio et al, 2007;Rosenzweig et al, 2003;Swink et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…The general body of literature on logistics services (Bradley, 1994;Sum and Teo, 1999, Panayides, 2004, Gopal and Cline, 2007 confirms our assumption. Moreover, the few studies focused on this specific issue explicitly draw a clear connection between services and capabilities both in the logistics (Lynch et al, 2000) and supply chain management field (Tracey et al, 2005). Although logistics tasks may not be limited to the logistics services offered by 3PLs to the market, this connection allows us to measure logistics capabilities in an objective way.…”
Section: Logistics Capabilities Refer To the Ability Of An Organisatimentioning
confidence: 99%
“…Good quality packaging with enhanced labelling could positively impact the economic performance of SC members (Tracey, et al 2005) through cost savings due to reduced packaging waste (Carter & Rogers 2008). Packaging of good quality is likely to become increasingly important as regulatory and/or consumer demands for returnable or recyclable packaging increase (Angell & Klassen 1999).…”
Section: Product Quality Indicatorsmentioning
confidence: 99%